Oxytocin differentially modulates pavlovian cue and context fear acquisition - Cavalli, Juliana; Ruttorf, Michaela; Flor, Herta (Social cognitive and affective neuroscience, 2017)
Fear acquisition and extinction have been demonstrated as core mechanisms for the development and maintenance of mental disorders, with different contributions of processing cues vs contexts. The hypothalamic peptide oxytocin (OXT) may have a prominent role in this context, as it has been shown to affect fear learning. However, investigations have focused on cue conditioning, and fear extinction. Its differential role for cue and context fear acquisition is still not known. In a randomized, double-blind, placebo (PLC)-controlled design, we administered an intranasal dose of OXT or PLC before the acquisition of cue and context fear conditioning in healthy individuals (n = 52), and assessed brain responses, skin conductance responses and self-reports (valence/arousal/contingency). OXT compared with PLC significantly induced decreased responses in the nucleus accumbens during early cue and context acquisition, and decreased responses of the anterior cingulate cortex and insula during early as well as increased hippocampal response during late context, but not cue acquisition. The OXT group additionally showed significantly higher arousal in late cue and context acquisition. OXT modulates various aspects of cue and context conditioning, which is relevant from a mechanism-based perspective and might have implications for the treatment of fear and anxiety.